PENGARUH SUPLEMENTASI VITAMIN D TERHADAP KADAR HDAC2 PADA PASIEN PPOK STABIL - Adyan Donastin; Danny Irawan; Effendy; Rifky Dwi Aditya Iryawan; Nuzlan Nuari; Betta Mega Oktaviana; Devy Yahya; Akbar Reza Muhammad (Klinikal Sains : Jurnal Analis Kesehatan, 2026)
Chronic Obstructive Pulmonary Disease (COPD) is the third leading cause of global mortality, characterised by persistent lung inflammation partly associated with reduced levels of histone deacetylase 2 (HDAC2). Since vitamin D may theoretically modulate HDAC2, this preliminary study aimed to evaluate the effect of vitamin D supplementation on HDAC2 levels in stable COPD patients at Jemursari Islamic Hospital, Surabaya. A one-group pre–post test experimental design without a control group was used. Five stable COPD patients meeting the inclusion criteria received 5000 IU of cholecalciferol daily for three months, with serum 25(OH)D₃ and HDAC2 measured before and after the intervention by ELISA and analysed using a paired t-test (p<0.05 considered significant). Supplementation significantly increased 25(OH)D₃ (7.63 ± 2.73 to 14.26 ± 2.43 ng/mL; p=0.023) and HDAC2 (1.50 ± 1.02 to 3.90 ± 1.39 ng/mL; p=0.006), whereas all pulmonary function parameters showed only an increasing trend without reaching statistical significance (all p>0.05). Vitamin D supplementation was associated with increased HDAC2, suggesting a potential molecular anti-inflammatory effect not yet accompanied by significant functional improvement. Given the very small sample (n=5) and the absence of a control group, these findings are hypothesis-generating and require confirmation in larger controlled trials before vitamin D can be considered as adjunctive COPD therapy.